Peran Dana Desa dalam Pembangunan Infrastruktur Pertanian di Desa Wringinpitu - Khoirunisa, Al Fira; Ti'anatud Diniati, Bintis; Risma Elvinda, Vika; Nur Aini, Ela; Yuana Putri, Ismawati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Agricultural infrastructure development is a fundamental requirement for villages to support the smooth running of production activities. This study aims to describe the planning process, implementation, and results of agricultural infrastructure development in Wringinpitu Village, Mojowarno District, Jombang Regency, from 2021 to 2023. The research used qualitative methods through interviews, observations, and searches of official village government documents. The results showed that Wringinpitu Village continuously allocated part of the Village Fund for the construction of road retaining walls, irrigation channels, farm roads, culverts, and paved roads. The planning stage was carried out through participatory forums from the hamlet level to the Village Consultative Meeting, so that the proposed development reflected the needs of the community, especially farmers. The activities were carried out by the Activity Implementation Team with the involvement of local residents through labour-intensive programmes. This study also found obstacles in the form of rainy weather conditions and land ownership issues that affected the smooth running of the work. Overall, the development of agricultural infrastructure in this village shows that the seriousness of the village government and community involvement are crucial in improving road access, irrigation water distribution, and agricultural productivity.